2016
DOI: 10.3390/foods5020032
|View full text |Cite
|
Sign up to set email alerts
|

Macular Pigment Optical Density and Measures of Macular Function: Test-Retest Variability, Cross-Sectional Correlations, and Findings from the Zeaxanthin Pilot Study of Response to Supplementation (ZEASTRESS-Pilot)

Abstract: We report on the short-term test-retest baseline variability in macular function tests in ZEASTRESS-Pilot participants (n = 18), on their cross-sectional correlation with macular pigment optical density (MPOD), and on the effects of four months (FUV4) of 20 mg/day zeaxanthin (ZX), followed by a four-month washout (FUV8; n = 24, age 50–81 years old). Outcomes included: MPOD at 0.5 and 2.0 deg eccentricity (MPOD-0.5 and -2.0); contrast sensitivity (CS); pattern-reversal electroretinogram (PERG) amplitude; dark-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…In to a mean value of 15dB, 21dB, 26 dB in-order to low, mid, high ranges of MPOD value. Previous studies have shown a strong correlation between Contrast sensitivity and Macula pigments [17,32] this study shows a significant decrease of contrast sensitivity with lowering of MPOD in p > 0.05 and the results are consistent with J. Loughmans' findings in Macular pigment and its contribution to visual performance and experience [17]. Low range MPOD group shows very low levels of contrast sensitivity compared to other groups.…”
Section: Relationship Between Macula Pigment Optical Density and Visusupporting
confidence: 90%
“…In to a mean value of 15dB, 21dB, 26 dB in-order to low, mid, high ranges of MPOD value. Previous studies have shown a strong correlation between Contrast sensitivity and Macula pigments [17,32] this study shows a significant decrease of contrast sensitivity with lowering of MPOD in p > 0.05 and the results are consistent with J. Loughmans' findings in Macular pigment and its contribution to visual performance and experience [17]. Low range MPOD group shows very low levels of contrast sensitivity compared to other groups.…”
Section: Relationship Between Macula Pigment Optical Density and Visusupporting
confidence: 90%
“…A detailed time course of XP repletion in two volunteers has shown a steady increase for 140 days after initiation of supplementation, followed by a plateau or slight decrease to 1 year or more 157. Many studies report that dietary supplementation results in higher MPOD (measured behaviorally or via several imaging technologies) at the earliest time points tested, typically 2 to 4 months and depending on the dose and baseline XP levels in test subjects 131,158169. XP removal is less well documented, with limited data suggesting stable, slightly decreasing, or baseline MPOD 157,169.…”
Section: Considering Dietary Delivery Of Xanthophyll Pigmentmentioning
confidence: 99%
“…Associations between rod-mediated vision and MPOD have also been reported for both younger and older normal eyes, 6,15 although one study reported no association. 21…”
Section: Introductionmentioning
confidence: 99%